O negócio atlântico : as redes comerciais portuenses e as novas geografias do trato internacional (séculos XVI-XVII) - Barros, Amândio Jorge Morais (História: revista da Faculdade de Letras da Universidade do Porto, 2018)
This work introduces the part played by the Portuguese Northwest centres in the construction of the Atlantic system due to the international traffic developed from its ports. One discusses here traditional historiographical interpretations, namely in what concerns the amplitude of the trade developed in the beginning of the Early Modern Period by commercial agents who can be positioned outside the Iberian imperial schemes, and the centrality of the economic spaces in the same period.